Plant ethnoveterinary practices in two pyrenean territories of catalonia (iberian peninsula) and in two areas of the balearic islands and comparison with ethnobotanical uses in human medicine. - Carrió, Esperança; Rigat, Montse; Garnatje, Teresa; Mayans, Marina; Parada, Montse; Vallès, Joan (Evidence-based complementary and alternative medicine : eCAM, 2012)
This paper presents the results of an ethnobotanical study centred in veterinarian uses in two Catalan Pyrenean regions (Alt Empordà -AE- and High River Ter Valley -AT-, Iberian peninsula) and two Balearic Islands areas (Formentera -FO- and northeastern Mallorca -MA-). In the areas studied, 97 plant species have been claimed to be useful for veterinary purposes. A total of 306 veterinary use reports have been gathered and analysed. The ten most reported plants are Tanacetum parthenium (24 use reports), Parietaria officinalis (15), Ranunculus parnassifolius (14), Meum athamanticum (13), Olea europaea (13), Quercus ilex (12), Ruta chalepensis (12), Sambucus nigra (10) and Thymus vulgaris (10). According to comprehensive reviews, a high number of novelties for plant ethnoveterinary are contributed: 34 species and one subspecies, 11 genera, and three families have not been reported in previous works in this field, and 21 species had only been mentioned once. Several ethnoveterinary uses are coincidental with those in human medicine. Although ethnoveterinary practices are less relevant than in the past in the territories considered, as in all industrialised countries, the knowledge on plant properties and applications is still rich and constitutes a large pool of evidence for phytotherapy, both in domestic animals and humans.
The following values have no corresponding Zotero field: accession-num: 22829861
Keywords: Ethnobotany; medicinal plants (PG); Veterinary medicine